Improved protocols for Aspergillus minimal medium: trace element and minimal medium salt stock solutions - Terry W Hill; Etta Kafer (Fungal Genetics Reports, 2001)
Simplified protocols for ingredients of Aspergillus minimal medium (MM) are presented. These either do not change the final composition of MM or at most involve only minor modifications which, in extensive comparative tests, have not shown any effects on growth patterns of all strains/cultures tested.